Cultural Production and Social Movements After the Arab Spring Nationalism, Politics, and Transnational Identity - Mohamed, Eid; El-Desouky, Ayman (Bloomsbury Academic, 2021)
This book is available open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. The so-called Arab Spring challenged conventional wisdom and certainties about the Arab world where its effects continue to be felt as well as in the diaspora. This book provides an original contribution to current social and cultural theory on Arab social movements by giving a fuller historical and critical treatment of contemporary artistic and cultural production from the region and beyond. Thematically structured and covering culture, media, politics, and literary studies, the book uses a range of theoretical material that engages readers in three key ways. First, it adopts a critical standpoint with respect to the term "Arab Spring," recognizing the multiple interpretations and varied geographical, historical, and political realities of the term. Second, its focus on carefully selected case studies - namely, Egypt, Tunis, Syria, and Yemen - adds depth to analysis of the cultural, literary and artistic dimensions that operate fluidly across the Arab world. Third, it presents a methodological case study for the growing community of researchers involved in interdisciplinary education. Together, the contributors to the book show how the interplay of politics, culture, and media across varied locations has and continues to shape emergent Arab social forms and a region on the cusp of historical and cultural change.